Unprecedented tropical cyclone in temperate‐boreal ecotone drives declines in emergent conifers and canopy complexity - Kirill Korznikov; Tatyana Petrenko; Violetta Dzizyurova; Dmitriy Kislov; Jiří Doležal; Jan Altman (Ecology, 2025)
Poleward shifts in tropical cyclone (TC) activity have introduced unprecedented disturbances to Northeast Asia's boreal and temperate‐boreal ecotone forests. As TCs migrate northward, they increasingly influence previously unaffected regions, yet their impacts on forest structure and species composition remain poorly understood. This study examines TC Maysak (2020), the most intense cyclone recorded in the ecotone forests near the Chinese–Russian border, and its effects on tree vulnerability and canopy structure. Using high‐resolution drone‐based orthophotographs, we analyzed fallen tree dimensions across four affected sites within protected forests, identifying key differences between coniferous and broadleaf species. Tall emergent conifers, including Manchurian fir ( Abies holophylla ) and Korean pine ( Pinus koraiensis ), were disproportionately susceptible to windthrow, with mean fallen heights exceeding the average canopy height by 4.88 ± 0.20 m (13.62 m maximally). In contrast, broadleaf species such as Mongolian oak ( Quercus mongolica ) exhibited minimal height variation relative to the canopy average. Our findings highlight TCs as emerging disturbance agents in Northeast Asia's temperate‐boreal ecotone, preferentially removing emergent conifers, simplifying canopy structure, and promoting broadleaf dominance. As TC activity intensifies under global climate change, these disturbances may accelerate forest transitions in climatically sensitive ecotone forests.